2022
DOI: 10.1038/s41467-022-31757-8
|View full text |Cite
|
Sign up to set email alerts
|

Rare loss of function variants in the hepatokine gene INHBE protect from abdominal obesity

Abstract: Identifying genetic variants associated with lower waist-to-hip ratio can reveal new therapeutic targets for abdominal obesity. We use exome sequences from 362,679 individuals to identify genes associated with waist-to-hip ratio adjusted for BMI (WHRadjBMI), a surrogate for abdominal fat that is causally linked to type 2 diabetes and coronary heart disease. Predicted loss of function (pLOF) variants in INHBE associate with lower WHRadjBMI and this association replicates in data from AMP-T2D-GENES. INHBE encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 77 publications
2
39
0
1
Order By: Relevance
“…Burden scans have shown great promise for identifying disease mechanisms and therapeutic targets [39, 61]. Through an independent assessment of 20 computational variant effect predictors, this study identified two predictors, VARITY and REVEL, as corresponding most closely with human traits in a large prospective cohort, suggesting that they might also enhance the power of rare-variant burden scans for detecting gene-trait associations.…”
Section: Discussionmentioning
confidence: 89%
“…Burden scans have shown great promise for identifying disease mechanisms and therapeutic targets [39, 61]. Through an independent assessment of 20 computational variant effect predictors, this study identified two predictors, VARITY and REVEL, as corresponding most closely with human traits in a large prospective cohort, suggesting that they might also enhance the power of rare-variant burden scans for detecting gene-trait associations.…”
Section: Discussionmentioning
confidence: 89%
“…It remains unknown from which cells activin B or C is derived to act on ALK7 in adipocytes. On the other hand, mutations of genes encoding hepatokine, activin E, and ALK7 are commonly associated with fat distribution and diabetes risk in humans [31,32], although there is no direct biochemical evidence for their ligand-receptor relationship.…”
Section: Activins and Gdf3 As Alk7 Ligandsmentioning
confidence: 99%
“…A recent work using inhibitors of Smad Activin AB, B, and C can activate ALK7 signaling both in heterologous cells and in adipocytes [5,23,30], although it is unknown from which cells these activins are derived to act on ALK7 in vivo. Variants in activin E produced from liver and ALK7 are associated with a lower waist-to-hip ratio in humans [31,32], although there is no direct evidence for the ligand-receptor relationship between them. GDF3 can also activate ALK7 signaling both in heterologous cells and in adipocytes [11,25].…”
Section: Activins and Gdf3 As Alk7 Ligandsmentioning
confidence: 99%
“…Expression quantitative trait loci (eQTLs) analysis in relevant tissues together with exome sequencing further highlighted enrichment in the brain- or peripheral-tissue-related pathways as a determinant for BMI or WHRadjBMI, respectively. For example, the predictive loss of function (pLoF) of adipocyte-expressed PLIN1 , INSR , ACVR1C and PDE3B and liver-expressed INHBE variants are associated with increased gfSAT and healthy metabolic phenotypes [ 61 , 70 , 71 ]. Importantly, WHRadjBMI-associated loci exhibit heritability and effect size stronger in women than men with one-third of all signals sexually dimorphic [ 72 ].…”
Section: Determinants Of the Fat Depot Repartition According To The Sexmentioning
confidence: 99%
“…The GWAS highlight several peripheral tissue- and cell-enriched pathways as determinants for WHRadjBMI suggesting that WAT intrinsic cell composition, function and remodeling are key contributors in fat depot repartition [ 61 , 70 , 71 ]. Recent single-cell atlas of human and mouse WAT provides a transcriptional basis of the heterogeneity in subsets of resident progenitors and adipocytes with fat depot-specific prevalence and functions [ 82 ].…”
Section: Determinants Of the Fat Depot Repartition According To The Sexmentioning
confidence: 99%